Antimicrobial Policy in Indonesia within the One Health Context: Literature Analysis and Implementation Challenges - Puji Lestari; Puput Oktamianti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Antimicrobials such as antibiotics, antivirals, antifungals, and antiparasitics are vital for treating infections in humans, animals, and plants. Antimicrobial Resistance (AMR) occurs when microorganisms become resistant to these drugs, posing a serious global threat. In Indonesia, high rates of infectious diseases increase the risks associated with AMR, highlighting the need for effective control measures. This study reviews research on efforts to control antimicrobial resistance in Indonesia within the One Health context, analyze related policies, and identifies key implementation challenges to provide recommendations for improvement. Method: A literature review was conducted, identifying 1,029 articles from databases including EBSCOHost, ProQuest, PubMed, and Google Scholar. After screening and applying inclusion criteria, 14 relevant articles were selected for analysis to evaluate policies related to AMR in Indonesia and their alignment with the One Health approach. Result: The findings showed that the increase in antimicrobial resistance (AMR) in Indonesia is mainly due to the misuse of antimicrobial drugs in different areas. While there are policies in place, putting them into practice has proven difficult, especially in the health sector, which faces more challenges than the livestock and environmental sectors. These results highlight the need for better coordination and alignment of policies across all sectors. Conclusion: Although current AMR policies in Indonesia incorporate the One Health approach, significant challenges remain, including limited resources, insufficient guidelines, and weak coordination among sectors. Strengthening collaboration between health, agriculture, and environmental sectors and improving monitoring systems is essential for effective AMR control in Indonesia.